THE IMPACT OF CURRENCY RATE VOLATILITY ON ALGERIA'S POVERTY RATES (2004 AND 2022) - Ghaleb Amad Omran Hamad; Eman Abdalkadhem Jabbar Al-kuraity (Scholar Express Journals, 2025)
The influence of exchange rates on poverty levels is significant. We will improve Algeria's production system by implementing an economic strategy that aims to keep the local currency exchange rate stable relative to the dollar. This will assist in preventing hyperinflation and bring about economic stability. As a result, it will boost local exports to the global market, which will boost domestic output and lower unemployment rates. It will also target poverty by hiring as many unemployed people as possible in organizations, businesses, and manufacturing facilities across a range of specialties. The study sought to determine how exchange rates affected Algeria's poverty levels. It came to several conclusions, the most notable of which is that economic policy had succeeded in stabilizing the exchange rate relative to other currencies, particularly the dollar, and generating economic growth that helped lower Algeria's poverty levels. In order to reduce the phenomenon of poverty in Algeria, the research suggests that economic policies aimed at increasing production capacities and protecting the value of the local currency from deterioration be put in place. The government agencies in charge of putting these policies into effect must also set and specify a time frame for implementation, find a way to ensure that the implementation and follow-up of implementation are effective, and work to create a database of people who are below the poverty line in order to create job opportunities for the unemployed workforce.
Keywords: Exchange rate; Poverty; volatility